Feeling (for) the other? Fiction, Empathy, and the Critical Medical Humanities (KULT_online, 2020)
Anne Whitehead’s 2017 monograph, recently published as paperback with Edinburgh UP (2019) titled Medicine and Empathy in Contemporary British Fiction: An Intervention in the Medical Humanities, performs a highly relevant intervention into mainstream modes of reading fiction within the medical humanities. Providing a timely critique of the celebratory use of fiction in the field, she focuses on empathy, resituating it away from individual consciousness, and arguing for a more politicized view. This kind of critical literary analysis opens up further possibilities for the medical humanities that should all but limit itself to the study of literary fiction as such.